SOSIALISASI PERLINDUNGAN HUKUM EKSPRESI BUDAYA TRADISIONAL SENI UKIR TULANG DI DESA TAMPAKSIRING KABUPATEN GIANYAR - Jayantiari, I.G.A.M.R.; Aryani, N.M.; Indrawati, A.A.S. (Buletin Udayana Mengabdi, 2022)
The purpose of this service is to be able to realize legal awareness about the importance of legal protection for works of bone carving art in Tampaksiring Village as a hereditary creation idea that exists in the community. The results of local carving crafts have even become icons of the creative industry supporting Bali tourism. The target of the service is aimed at the group of bone carving artisans in Tampaksiring Village, Gianyar Regency, which is currently in the process of fostering creative economy efforts in the tourism sector by the government. An understanding of the importance of protecting a copyrighted work containing a hereditary heritage as a cultural expression of intellectual property rights must be known by craftsmen. The important target set is directed at legal awareness of copyrighted works to start immediately in order to avoid plagiarism and their unique bone carving art designs by irresponsible parties. The lecture, discussion and question and answer methods as well as direct coaching by providing concrete instructions in registering works are the core of this community service. The realization of the service received a positive response with the presence of craftsmen regarding the registration of their copyrighted works so as to facilitate follow-up in realizing the protection of intellectual property rights as stipulated in Law no. 28 of 2014 concerning Copyright. Keywords: Socialization, Legal Awareness, Legal Protection, Traditional Cultural Expression